Potencial natural de erosão hídrica para o estado de Mato Grosso - Di Raimo, Luis Augusto Di Loreto (2017)
The objective of the present work was to estimate the spatial variability of the natural potential erosion (NPE) for Mato Grosso state. The specifics objectives were: estimate the spatial variabilities of erosivity (EI30 and R), erodibility (K) and obtain a map for topografic factor LS. After obtaining the maps, these were combined (multiplied) using ArcGIS software. This combination generated as final product the PNE map. The mean value of R for State is classified as high and equivalent to 8835 MJ mm ha-1 year-1 . 91% of annual erosivity is concentrated in the months of October to April. The Mato Grosso state has in most of its territory (98%) low and medium erodibility soils. The most critical areas (high erodibility) occupy 1.95% of the State. The values of topographic factor LS ranged from 0 to 4.6, with predominance of values ranging from 0 to 1 (95.13% of state territory). In the Mato Grosso state occur soils with PNE in the low, middle and high classes (20%, 58% and 22%, respectively). The areas of high PNE are considered critical and present higher proportions in the northwest (46.69%), northern (32.70%) and western (30.06%) macro regions. The large extensions of high PNE, in north of the west macro region, used with agriculture, characterize a problematic region, where the annual rates of soil loss should be monitored.